Case report: positive pitfalls of PSMA PET/CT: diagnostic challenges in degenerative bone lesions including MODIC type 1 - Moukaddam, Hicham; El Saheb, Ghida; Omran, Nadine; El Ghawi, Nour; Abi Ghanem, Alain; Haidar, Mohamad (Frontiers in Nuclear Medicine, 2024)
Prostate-specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) is an imaging technique that has demonstrated high sensitivity and specificity in detecting prostate cancer and its metastasis, especially in the bones. This case describes a 60-year-old man who presented for increased prostate-specific antigen (PSA) level and underwent [68Ga]gallium-PSMA-11 PET/CT imaging for better disease assessment. 68Ga-PSMA-11 PET/CT revealed numerous radiotracer-positive lesions in both prostate lobes with associated sclerotic lesions on L4 and L5, but only L5 showed increased radiotracer avidity raising the possibility of metastasis. Magnetic Resonance Imaging (MRI) raises the possibility of aggressive MODIC type 1 lesion vs. infectious/inflammatory process. A biopsy of the radiotracer avid area was performed and showed no evidence of metastasis. The final diagnosis was aggressive MODIC type 1, in keeping with the false positive result of 68Ga-PSMA-11 PET/CT. This example demonstrates the possible limitations of 68Ga-PSMA-11 PET/CT, particularly in detecting bone metastases, and emphasizes the need for cautious interpretation and additional study to improve its diagnostic accuracy. Understanding and resolving these limitations is critical for increasing the accuracy of PSMA PET/CT in prostate cancer management.